The chromatin remodeler SRCAP promotes self‐renewal of intestinal stem cells. (25th May 2020) - Ye, Buqing; Yang, Liuliu; Qian, Guomin; Liu, Benyu; Zhu, Xiaoxiao; Zhu, Pingping; Ma, Jing; Xie, Wei; Li, Huimu; Lu, Tianku; Wang, Yanying; Wang, Shuo; et al.
Abstract: Lgr5 + intestinal stem cells (ISCs) exhibit self‐renewal and differentiation features under homeostatic conditions, but the mechanisms controlling Lgr5 + ISC self‐renewal remain elusive. Here, we show that the chromatin remodeler SRCAP is highly expressed in mouse intestinal epithelium and ISCs. Srcap deletion impairs both self‐renewal of ISCs and intestinal epithelial regeneration. Mechanistically, SRCAP recruits the transcriptional regulator REST to the Prdm16 promoter and induces expression of this transcription factor. By activating PPARδ expression, Prdm16 in turn initiates PPARδ signaling, which sustains ISC stemness. Rest or Prdm16 deficiency abrogates the self‐renewal capacity of ISCs as well as intestinal epithelial regeneration. Collectively, these data show that the SRCAP‐REST‐Prdm16‐PPARδ axis is required for self‐renewal maintenance of Lgr5 + ISCs. Synopsis: Chromatin remodeling represents a critical layer of epigenetic regulation in adult stem cells. Here, molecular and in vivo characterization reveals that the chromatin remodeler SRCAP recruits the transcriptional regulator REST to induce Prdm16 transcription, which initiates PPARδ signaling to sustain "stemness" of mouse intestinal stem cells (ISCs). SRCAP is required for self‐renewal maintenance of Lgr5 + ISCs and intestinal epithelial regeneration. SRCAP associates with REST to form a Yeats4‐containing transcriptional activator complex in ISCs, rather than an HCLR repressor complex. SRCAP recruits REST to the Prdm16 promoter to initiate its transcription. Prdm16 transcription factor initiates PPARδ expression to promote self‐renewal of ISCs. Abstract : SRCAP recruitment of transcriptional coregulator REST to the Prdm16 promoter induces its expression, in turn activating PPARδ expression and signaling to sustain ISC self‐renewal.